La crítica leibniziana a la doctrina teleológica de Descartes - Arana, Juan (2014)
This paper analyzes the divergences between Leibniz and Descartes concerning the possibility and use of teleological explana- tions, both in metaphysics and physics. Descartes is skeptical about discovering God’s aims in the creation of the world and yet he uses teleological proofs when trying to unveil the laws of nature and the constitution of living beings. Leibniz is far more audacious in dealing with theological aspects of teleological explanation, but far more cautious when using it in the exploration of the secrets of nature, although willing to recognize the importance of this second aspect.